Convergence of Light and ABA signaling on the ABI5 promoter. - Dongqing Xu; Jigang Li; Sreeramaiah N Gangappa; Sreeramaiah N Gangappa; Chamari Hettiarachchi; Fang Lin; Mats X Andersson; Yan Jiang; Xing Wang Deng; Magnus Holm (PLoS Genetics, 2014)
Light is one of the most important environmental cues regulating multiple aspects of plant growth and development, and abscisic acid (ABA) is a plant hormone that plays important roles during many phases of the plant life cycle and in plants' responses to various environmental stresses. How plants integrate the external light signal with endogenous ABA pathway for better adaptation and survival remains poorly understood. Here, we show that BBX21 (also known as SALT TOLERANCE HOMOLOG 2), a B-box (BBX) protein previously shown to positively regulate seedling photomorphogenesis, is also involved in ABA signaling. Our genetic data show that BBX21 may act upstream of several ABA INSENSITIVE (ABI) genes and ELONGATED HYPOCOTYL 5 (HY5) in ABA control of seed germination. Previous studies showed that HY5 acts as a direct activator of ABI5 expression, and that BBX21 interacts with HY5. We further demonstrate that BBX21 negatively regulates ABI5 expression by interfering with HY5 binding to the ABI5 promoter. In addition, ABI5 was shown to directly activate its own expression, whereas BBX21 negatively regulates this activity by directly interacting with ABI5. Together, our study indicates that BBX21 coordinates with HY5 and ABI5 on the ABI5 promoter and that these transcriptional regulators work in concert to integrate light and ABA signaling in Arabidopsis thaliana.